The association of pri-miRNA- 26a1 rs7372209 polymorphism and Preeclampsia susceptibility - Fatemeh Eskandari; Mahnaz Rezaei; Abbas Mohammadpour-Gharehbagh; Batool Teimoori; Minoo Yaghmaei; Mehrnaz Narooei-Nejad; Saeedeh Salimi (Clinical and Experimental Hypertension, 2019)
MicroRNAs (miRNAs) are a class of noncoding small RNAs which regulate gene expression through post-transcriptional repression or degradation of messenger RNA. They play very important roles in various biological processes including growth, differentiation, and proliferation, as well as apoptosis, angiogenesis, and metabolism. Therefore, in the present study, we evaluated the possible effect of functional rs7372209C/T polymorphism in the 5ˊ- region of pri-miRNA- 26a1gene on preeclampsia(PE) susceptibility. This case-control study was conducted on 219 PE women and 204 unrelated healthy controls. The amplification refractory mutation system-polymerase chain reaction method was used for rs7372209C/T genotyping. The pri-miRNA- 26a1 rs7372209CT genotype was associated with decreased PE risk (OR, 0.5 [95% CI, 0.3–0.8], P = 0.001). The frequency of rs7372209TT genotype did not differ between two groups. In addition, the pri-miRNA- 26a1 rs7372209 polymorphism was associated with lower risk of PE in dominant model (CT+TT vs CC) (OR, 0.5 [95% CI, 0.4–0.8], P = 0.002). Although there was no significant difference between mild and severe PE women according to rs7372209CT genotype, the differences between mild and severe PE groups with controls remained significant. The frequency of pri-miRNA-26a1 rs7372209CT genotype was not different between late-onset PE and early onset PE groups. The present study showed for the first time that the pri-miRNA- 26a1 rs7372209 polymorphism was associated with lower risk of mild and severe PE in the dominant model and this polymorphism could be a protective factor for PE susceptibility.